Community-based music making and music-based community making: The case of the We Are All Musicians (waam) project - Stewart, Jesse (Circuit, 2024)
In this essay, percussionist and community arts worker Jesse Stewart discusses his work in the field of participatory creative music through We Are All Musicians (waam), an organization and ongoing research-creation project he started in 2012. waam is dedicated to making music as broadly accessible as possible, particularly among communities that have experienced barriers to making music, notably children and adults living in low-income situations, individuals with disabilities of various kinds, and the elderly. Stewart discusses several participatory creative projects that have resulted from partnerships between waam and community organizations including Regina Street Alternative School (formerly Regina Street Public School) in Ottawa; Being Studio (formerly H’Art of Ottawa); the Alzheimer’s Society of Ottawa, Artswell, the Bruyère Continuing Care Centre in Ottawa, and the National Arts Centre. He goes on to discuss several interactive music/sound installations that he has set up in public spaces to facilitate interactive improvisatory musical interaction across various forms of difference. The essay concludes with a discussion of some waam initiatives that took place online during the covid-19 pandemic, using networked improvisation to facilitate musical interaction and community formation across both difference and distance.